A spiral back-off mechanism in IEEE 802.15.4 media access control (MAC) protocol for smart grid applications - Bari, S. M. Sadakatul (Kulliyyah of Engineering, International Islamic Universiy Malaysia, 2017)
Smart grid is an envisioned intelligent, robust and resilient energy delivery network of 21st centuries. Advanced Metering Infrastructure (AMI), Demand Response, Distributed and Renewable energy integration, Electric Vehicle integration and distribution automation are some of the key applications that need to be supported by smart grid. To realize these, smart grid requires a robust, reliable communication network to exchange real time data among the intelligent devices, smart meters etc. that are deployed in the grid area (generation, distribution and customer premises). A Wireless Sensor Network (WSN) is one of the key enabling technologies to support these smart grid applications. IEEE 802.15.4 standard provides a low cost, low power Wireless Sensor Networks (WSNs) solution for this purpose. This standard defines media access control (MAC) protocol that employs slotted Carrier Sense Multiple Access/Collision Avoidance (CSMA/CA) with binary exponential backoff algorithm (BEB) as a means of collision avoidance without considering any traffic requirements. However, in the context of smart grid, WSNs need to support multiple applications concurrently with different delay and reliability requirements. In this thesis, two novel backoff mechanisms are proposed namely BEB with Priority and Spiral Backoff. In the first approach, sensor nodes are classified as four types (protection, control, monitoring and billing/others) and priorities are given accordingly. In the second approach, Applications traffics are classified as four access categories (protection, control, monitoring and billing/others) and spiral backoff is used to prioritize the applications. Discrete Markov chain based analytical models are developed and mathematical expression for reliability and average delay is derived. Numerical solutions have been done using MATLAB software. The numerical results show that when number of nodes are 20, the average delay for protection, control, monitoring and billing nodes for standard IEEE CSMA/CA-BEB are around 16ms, 17ms ,17ms, 18ms whereas for BEB with node priority are 6ms,17ms, 31ms and 57ms and for spiral backoff 6ms, 9ms, 13ms and 19ms respectively. The delay reduction for the node with protection traffic around 36%. The reliability for standard IEEE CSMA/CA-BEB are 95%, 92%, 90% and 92%, for BEB with node priority are 98%, 93%, 94% and 97% and for CSMA/CA-Spiral is around 99% respectively. In the case of multi-application, the average delay of standard IEEE CSMA/CA-BEB are around 14ms for all four applications traffic whereas CSMA/CA-Spiral backoff, the average delay of the protection traffic is under 9ms (an reduction around 39%which is very important for time critical smart grid applications) and for the control traffic is close to 14ms. The average delays for the monitoring and others nodes are become around 22ms and 32ms respectively.